ANALISIS STRATEGI INOVASI BERKELANJUTAN PADA UMKM DI KOTA JAMBI - Hansen Rusliani; Kurniyati; Widia (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
Sustainable innovation is a process in which aspects of sustainable development (environmental, social, economic) are integrated into enterprise systems as ideas are developed through research, development and commercialization. This applies to products, services and technologies as well as new business and organizational models.With UMKM actors creating a new innovation from UMKM products, every 2 UMKM actors that researchers take in Danau Teluk District and Serving District, Jambi City can create opportunities to create new innovations in UMKM products themselves. This study aims to find out how sustainable innovation strategies work for UMKM in Jambi City. The number of informants in this study were 2 people to find out sustainable innovation strategies both in terms of innovation and the constraints faced. The type of this research is descriptive qualitative with primary and secondary data types. Data collection techniques in this study were observation, interviews and documentation techniques, while for data analysis the researchers used data reduction analysis, data presentation and verification. The results of this study explain that sustainable innovation strategies for UMKM in Jambi City can be seen from several aspects, namely the lack of innovation by UMKM actors in Jambi City in making innovations in taste, packaging, and technology used in marketing products due to limited capital and human resources. as well as a lack of skills in creating a new idea in making products so that the resulting product is underdeveloped, therefore UMKM actors need to take part in events held by the government to motivate UMKM actors to make new innovations in products, there needs to be continuous innovation so that can create a new innovation so that the business being run can be known to the wider community and increase business income.